CLINICAL EFFICACY OF PELARGONIUM SIDOIDES EPS® 7630 IN COMPLEX THERAPY OF CHILDREN WITH CHRONIC ADENOIDITIS, WHO HAS UNDERGONE ADENOIDECTOMY - A. I. Kryukov; N. L. Kunelskaya; A. Yu. Ivoilov; G. N. Izotova; Yu. V. Luchsheva; A. I. Machulin; V. V. Yanovsky; I. I. Arkhangelskaya; V. P. Pakina; Z. N. Morozova (Медицинский совет, 2017)
200  children aged 4 to 12 years diagnosed with grade 3 adenoids, chronic adenoiditis, admitted for routine surgical intervention – adenoidectomy, have been examined and treated in the Pediatric ENT-pathology Department of the Moscow Department of Health L.I. Sverzhevskiy Otorhinolaryngology Healthcare Research Institute.2 groups of patients were formed depending on the treatment performed in the postoperative period. Group  I (active treatment): 100 children who underwent conservative treatment after adenoidectomy, including: tested/investigational drug – Umckalor solution (per os), dosing regimen: children aged from 4 to 6 years – 5–10 drops 3 times a day, aged from 6 to 12 years – 10 to 20 drops 3 times a day; topical decongestants (in the age-related dosage); silver proteinate (nasal drops in age-specific doses); secondand third-generation antihistamines (in the age-specific  doses). Group   II (control): 100  children, who received conservative therapy after adenoidectomy, including: antibacterial therapy (in the age-specific doses) (third-generation cephalosporins); topical decongestants (in the age-specific doses); silver proteinate (nasal drops in age-specific doses); secondand third-generation antihistamines (in the age-specific doses). In both groups, the course of postoperative therapy amounted to 7 days. The clinical studies have shown that in the early postoperative period the clinical efficacy of Umckalor as part of combined therapy in children, who underwent adenoidectomy, involves reducing the duration of reactive events, accelerating the healing of the postoperative nasopharynx wound. The combined antiviral, antibacterial, immunomodulatory, anti-inflammatory, mucolytic and secretory-motor effect of the drug allows Umckalor to be used as an alternative to antibacterial drugs as part of combined therapy in children who underwent adenoidectomy.